An auxiliary model based least squares algorithm for a dual-rate state space system with time-delay using the data filtering. Issue 2 (January 2016) - Ding, Feng; Liu, Ximei; Gu, Ya
Abstract: For dual-rate state space systems with time-delay, this paper combines the auxiliary model identification idea with the filtering technique, transforms the state space model into the identification model with different input and output sampling rates, and presents a filtering and auxiliary model based recursive least squares identification algorithm with finite measurement input–output data. Compared with the auxiliary model based recursive least squares algorithm, the proposed algorithm can generate more accurate parameter estimates and has a higher computational efficiency because the dimensions of its covariance matrices become small.